On the prospect of using cognitive systems to enforce data access control - Duarte, Fernando Fradique
Data access control is a field that has been a subject of a lot of research for many years, which has resulted in many models being designed. Many of these models are deterministic in nature, following set rules to allow or deny access to a given user. These are sufficient in fairly static environments, but they fall short in dynamic and collaborative settings where permission needs may change or user attributes may be missing. Risk-based and probabilistic models were designed to mitigate some of these issues. These take a user profile to determine the risk associated with a particular transaction or fill in any missing attributes. However, they need to be maintained as new security threats emerge. It is argued in this paper that cognitive systems, as part of a more general Cognitive Driven Access Control approach, can close this gap by learning security threats on their own and enhancing the security of data in these environments. The benefits and considerations to be made when deploying cognitive systems are also discussed.